“Dumping dilemma”: Rethinking Malaysia’s waste management crisis with sustainable finance solutions - A conceptual paper - Amran, Azzah; Mohamed, Zulkifli; Yaacob @ Othman', Azmahani (International Journal of Accounting, Finance and Business, 2025)
The rising importance of Environmental, Social, and Governance (ESG) principles has led to a greater focus on sustainable waste management practices across nations. This conceptual paper explores the alignment of waste management in Malaysia with sustainable finance, emphasizing the role of financial-based solutions to tackle mounting waste issues. Drawing on the Waste Hierarchy Model, the Theory of Waste Management, and the Theory of Planned Behavior (TPB), the paper outlines the core issues-such as landfill dependency and low recycling rates—and analyzes how financial incentives implemented in other commies could serve as effective policy interventions in Malaysia. This paper serves as a foundation for future empirical investigations into behavioral and policy mechanisms driving sustainable waste practices